2020
DOI: 10.1063/5.0008983
|View full text |Cite
|
Sign up to set email alerts
|

Solid and hollow metallic glass microneedles for transdermal drug-delivery

Abstract: Metallic microneedles are attractive for painless transdermal drug-delivery. However, fabrication techniques for metal microneedles are often complex and multi-step. In this study, a scalable manufacturing of metallic microneedle arrays is presented using thermoplastic drawing of metallic glasses. Microneedles with tunable lengths and tips are produced by controlling the rheology and fracture of metallic glass. The same drawing process can generate solid and hollow microneedles simply by varying the thickness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…As MNs create micro-sized channels in the epidermis layer, the type, shape, size, density, and length of needles should be carefully considered. 46 The close association between MN geometry and effective insertion has been shown that an increase in insertion depth of needle affects both deflections of the skin. Under these circumstances, maximum force is applied to the needle insertion due to reducing the shear forces.…”
Section: Mn Fabrication Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As MNs create micro-sized channels in the epidermis layer, the type, shape, size, density, and length of needles should be carefully considered. 46 The close association between MN geometry and effective insertion has been shown that an increase in insertion depth of needle affects both deflections of the skin. Under these circumstances, maximum force is applied to the needle insertion due to reducing the shear forces.…”
Section: Mn Fabrication Methodsmentioning
confidence: 99%
“… 51 Additionally, coated-MNs support various drug delivery possibilities in the one-treatment procedure of each needle in different drug solutions. 1 Previously, Hu et al 46 constructed a metallic glass solid MN by thermoplastic drawing technique. The needles were dip-coated in red-colored drug solution to examine in vitro drug delivery potential on porcine cutaneous tissue.…”
Section: Types Of Mn Devicesmentioning
confidence: 99%
“…MNs can be categorized into several types according to the mechanism of drug delivery [ 52 ], such as solid [ [59] , [60] , [61] ], hollow [ 61 , 62 ], coated [ [63] , [64] , [65] ], dissolving and hydrogel types. Usually, MNs are employed as a preprocessed stratagem, which could produce microchannels to improve drug diffusion through inserting and withdrawing the MNs on the skin.…”
Section: Classification Of Flexible Polymeric Patchesmentioning
confidence: 99%
“…In recent years, researchers found that the transdermal drug delivery system can provide long-term and sustained drug delivery, and it is a promising drug delivery system in the treatment of these chronic diseases ( Choudhary and Singh, 2021 ; Bose et al, 2021 ; Anantrao et al, 2021 ; Hanumanaik* et al, 2012 ). The transdermal drug delivery system works very simply, and it has become an important field due to its self-advantages such as avoidance of first-pass metabolism, stable and controlled blood level, ease of termination of drug action, long duration of actions, and no interference with gastric and intestinal fluid ( Chu et al, 2020 ; Fukuta et al, 2020 ; Hu et al, 2020 ; Sabri et al, 2020 ; Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%